High-performance asymmetric supercapacitor based on CNT-graphene hybrid gel and MnO2-graphene hybrid gel - Bay, Alvin Koon Teck (2013)
Supercapacitors have been, in recent times, touted as the next highly anticipated form of energy storage devices to be watched due to their many potential applications and outstanding properties. Literatures have shown supercapacitors to possess excellent power and energy densities, high rate capability, long shelf live, and high cycling stability. In this report, the performance of supercapacitors, in particular asymmetric supercapacitors, will be evaluated. In theory, by utilizing two different composite materials, namely the carbon nanotube-graphene hybrid gel (CNT-GHG) and manganese oxide-graphene hybrid gel (MGHG), the asymmetric supercapacitor will be able to benefit from the advantageous properties that each of them can offer and mitigate weaknesses that the individual components have when operating independently.